Imposition of Good Samaritan Laws to Improve Professionalism among Medical Practitioners - Ashraf, Aishath Iffa; Faiz, Najy; Ariffin, Adlina (Intellectual Discourse, 2017)
This paper discusses a legal-moral confl ict that exists in the medical fi eld which pertains to the duties of medical practitioners toward their patients. More specifi cally, it deliberates on paradoxical situations where medical practitioners are “legally permitted” to refuse rendering their services to the needy due to the principles entrenched in the law of negligence. This legal conundrum has created a moral ‘neglect’ on the part of the medical practitioners toward their patients who are in dire need of medical treatment. Hence, this paper argues that the concepts inherent in the Good Samaritan laws should be imposed on medical practitioners in Malaysia, particularly, since neglecting patients who urgently require medical attention transgresses the Islamic principle of helping ones neighbours and the needy, contravenes the Hippocratic Oath and infringes the conscience of a morally upright individual.